Pengaruh Deposits, BOPO Dan NIM Terhadap Profit Distribution Management Pada Bank Umum Syariah Yang Terdaftar di JII Periode 2011-2014 - Indri Dwidya Nurmalawaty Wat; Icih Icih; Sri Mulyati (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2019)
This study aimed to analyze the factors affecting the Profit Distribution Management at Commercial Bank of sharia (BUS) in Indonesia. The dependent variable used in this study is Profit Distribution Management. Independent variables used in this study, among others Deposits, BOPO and NIM. This study used a sample of Islamic banks listed in the Jakarta Islamic Index (JII) in the 2011-2014 period. Data were collected using the technique purposive sampling. The total sample used in this study were 8 Islamic Banks. Data analysis was performed with the classical assumption and hypothesis testing with multiple regression method. Results from this study showed that the variables Deposits and BOPO significantly negative effect on the Profit Distribution Management, while the NIM variables do not significantly affect the distribution Profit Managemen.